Why do wages become more rigid during a recession than during a boom? - Izumi Yokoyama (IZA Journal of Labor Economics, 2014)
This paper provides a theoretical and empirical analysis of the effect of performance-based layoffs on wage rigidity in the context of performance pay. In the model, it becomes optimal for firms to raise future regular pay to maintain workers' current efforts, which results in downwardly rigid regular pay under the threat of performance-based layoffs. Furthermore, it becomes optimal for firms to base wages less on workers' performance during recessions due to the lower value of productivity. Consequently, wages during recessions also become "rigid" (inflexible) with respect to performance. The Japanese panel dataset supported these theoretical implications.
Keywords: J30; J33; J63; 330; Wage rigidity; Performance pay; Performance-based layoffs